The Literacy and Technological Digitalization Improvement Of Z-Generation - yustinah, Yustinah; Setiawan, Anjar (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The literacy and technology digitalization improvement for Z-generation is carried out as a realization of digital development in all sectors, including higher education. The improvement of literacy and the digitalization of technology for Z-generation were examined through stages that include (1) introduction; (2) objectives; (3) implementation; (4) steps; (5) materials; (6) references; and (7) assessment and final evaluation. The research subjects consisted of 465 students currently taking the Indonesian Language course, with details as follows: 45 Public Health A students; 46 Public Health B students; 42 Public Health C students; 34 Public Health D students; 42 D3 Nursing students; 86 Nutrition A students; 86 Nutrition B students; and 84 Medical students. Research method—data collection using Google Forms. The results of this study indicate that the improvement of literacy and technology digitalization is balanced between planning at 61.23%, implementation at 52.81%, and evaluation at 54.2%. This shows a balance between the improvement of literacy and the technology digitalization of Z-generation. Balance occurs between knowledge and skills and between theory and practice in the enhancement of literacy and the digitalization of Z-generation technology.